2014
DOI: 10.1116/1.4896334
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effect for SnS thin films prepared by high-vacuum evaporation

Abstract: Thin films of SnS are deposited onto molybdenum-coated soda lime glass substrates using the high-vacuum evaporation technique at a substrate temperature of 300 °C. The as-deposited SnS layers are then annealed in three different media: (1) H2S, (2) argon, and (3) vacuum, for different periods and temperatures to study the changes in the microstructural properties of the layers and to prepare single-phase SnS photoabsorber films. It is found that annealing the layers in H2S at 400 °C changes the stoichiometry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…7,8 Various methods have been investigated for the preparation of high quality SnS lms, e.g. chemical vapor deposition (CVD), 1,9 atomic layer deposition (ALD), 3 thermal evaporation, [10][11][12][13] sputtering, 2,14,15 chemical bath deposition (CBD), 16 spray pyrolysis, 7,17,18 and electrochemical deposition (ED). 19,20 So far most successful methods of fabricating high quality SnS lms are related to simultaneous deposition of two elements and crystallization, 11,18 such as ALD which produced pure, stoichiometric and homogeneous SnS lms from the reaction of bis(N,N 0 -diisopropylacetamidinato)tin(II) [Sn(MeC(N-iPr) 2 ) 2 ] and H 2 S at 200 C and achieved the highest efficiency of 4.63% for SnS-based thin lm solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Various methods have been investigated for the preparation of high quality SnS lms, e.g. chemical vapor deposition (CVD), 1,9 atomic layer deposition (ALD), 3 thermal evaporation, [10][11][12][13] sputtering, 2,14,15 chemical bath deposition (CBD), 16 spray pyrolysis, 7,17,18 and electrochemical deposition (ED). 19,20 So far most successful methods of fabricating high quality SnS lms are related to simultaneous deposition of two elements and crystallization, 11,18 such as ALD which produced pure, stoichiometric and homogeneous SnS lms from the reaction of bis(N,N 0 -diisopropylacetamidinato)tin(II) [Sn(MeC(N-iPr) 2 ) 2 ] and H 2 S at 200 C and achieved the highest efficiency of 4.63% for SnS-based thin lm solar cells.…”
Section: Introductionmentioning
confidence: 99%
“… System Light power (mW cm −2 ) Short-circuit current density (mA cm −2 ) Ref. FTO-SnS: 0.1 M K 4 Fe(CN) 6 + 0.01 M K 3 Fe(CN) 6 100 0.45 This work FTO-SnS: 0.1 M Na 2 S 2 O 3 30 0.3 30 FTO-Cu: SnS: 0.1 M K 4 Fe(CN) 6 + 0.01 M K 3 Fe(CN) 6 60 1.2 36 FTO-SnS: 0.1 M K 4 Fe(CN) 6 + 0.01 M K 3 Fe(CN) 6 100 0.42 40 ITO-SnS: 0.5 M Na 2 SO 4 100 3 37 FTO-SnS: 0.1 M Na 2 S 2 O 3 30 1 41 FTO-SnS: I 3− /I − 100 0.087 42 ITO-SnS-TiO 2 : 0.5 M Na 2 S 100 1.5 43 FTO-SnS: I 3− /I − 100 0.07 44 SnO 2 -SnS: 0.1 M FeCl 3 100 0.65 47 FTO-SnS: 0.1 M FeCl 3 100 0.25 48 Mo-SnS: 0.1 M H 2 SO 4 100 0.01 49 FTO-SnS: 0.1 M Eu(NO 3 ) 3 100 0.017 50 <...>…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the relaxation of the film to the equilibrium state is accelerated by thermal annealing [9][10][11]. Some researchers have investigated the changes in the films' optical, structural, electrical, and photosensitivity properties depending on the annealing temperature and atmosphere [12][13][14]. SnS is a metal chalcogenide semiconductor with a band gap of 1.30 eV that can be used in various applications.…”
Section: Introductionmentioning
confidence: 99%